OC-035 Mechanism of Lactose Intolerance in Irritable Bowel Syndrome: Role of Anxiety, Mucosal Immunity and Visceral Hypersensitivity. (4th June 2013) - Long, Y; Yang, J; Zhu, Y; Cong, Y; Chu, H; Dai, N; Fried, M; Fox, M
Abstract : Introduction: Many patients, especially those with Irritable Bowel Syndrome (IBS), report food intolerance; however the mechanism underlying these "functional digestive symptoms" is unknown. We assessed the role of psychological factors, mucosal immune activation and visceral sensitivity on the development of lactose intolerance (LI) after ingestion of 20g lactose in IBS patients and healthy controls (HCs) with lactase deficiency: a validated, clinical experimental model of intolerance to poorly absorbed, fermentable foods (Yang et al Clin Gastro Hep 2013 in publication). Methods: IBS-D patients meeting Rome III criteria (n = 277) and age/sex matched HCs (n = 64) underwent a 20g lactose hydrogen breath test (LHBT) with measurement of hydrogen production, abdominal distention, and LI symptoms. Hospital Anxiety and Depression Score assessed psychologic state. Barostat measured rectal sensitivity. Additionally, 55 IBS-D patients and 18 HCs completed colonoscopy with colon and terminal ileum (TI) biopsies for quantification of mast cells (MCs), T lymphocytes, and enterochromaffin cells (ECC). Results: Hydrogen production and distention were similar in IBS patients and HCs during LHBT; however LI symptoms were more frequent in IBS (54% vs. 28%, P < 0.001), including bloating (39% vs . 14%, P < 0.001), borborygmi (39% vs. 22%, P = 0.010), pain (31% vs. 11%, P = 0.001) and diarrhoea (29% vs. 9%, P = 0.001). IBS patients were more anxious (p < 0.001) and had higher rectal sensitivity than HCs ( P = 0.001). Multivariate analysis indicated that hydrogen production increased the likelihood of bloating (OR2.2 (95%CI 1.1–4.4), P = 0.028) and borborygmi (OR12.4 (3.3–45.8), P < 0.001), but not objective distention ( P = 0.673). Visceral hypersensitivity also associated with bloating (OR6.6 (1.7–25.0), P = 0.005) and total symptom score (OR3.7 (1.3–10.9, P = 0.014). A planned subanalysis showed that, compared to IBS patients with no symptoms, those with LI were more anxious (p = 0.045) and more likely to have visceral hypersensitivity (p < 0.001). In those that had colonoscopy, IBS patients with LI (25/55 (45%)) had increased MCs (p < 0.006), T-cells and ECC (both p < 0.05) in proximal colonic and TI mucosa compared to patients without LI and HCs. Multivariate analysis indicated that total LI symptom score was associated with anxiety (r = 0.519, P < 0.001), MCs in terminal ileum (r = 0.650, P < 0.001) and visceral sensitivity (r = 0.629, P < 0.001). Conclusion: Gas production and sensitivity to luminal distension both contribute to digestive symptoms after lactose ingestion in patients with lactase deficiency. IBS-D patients with LI are characterised by anxiety, evidence of mucosal immune activation and visceral hypersensitivity. Disclosure of Interest: None Declared